UiTMLaw maintains its QS World University Rankings by Subject - UiTM, Faculty of Law (Faculty of Law, 2023)
The Faculty of Law UiTM (UiTMLaw) remains in the QS World University Rankings by Subject 2023, placed in the top 350 law schools worldwide. This achievement is a testament to the and combined efforts of UiTMLaw's members and is based on four key indicators: Academic Reputation, Employer Reputation Citations perpaper and H-lndex by QS Quacquarelli Symonds. This recognition highlights UiTMLaw's dedication to excellence and its commitment to producing high-quality graduates for the legal industry both in Malaysia and globally. The Dean and the entire UiTMLaw family express their deepest gratitude to the Vice-Chancellor or UiTM, the top management of UiTM, UiTM Global, student, staff, lecturers, alumni, collaborators, partners and friend for their unwavering support. The success of UiTMLaw servers as proof of its international standing. UiTMLaw remains committed to producing graduates who excel in the legal industy and contribute to the development of Malaysia legal landscape.